Language shift and maintenance among the Telugu community in the Klang Valley / Kathreine Deva Babu - Kathreine, Deva Babu (2016)

(untitled)
The Telugu language is an Indian language commonly spoken in the Indian states of Andhra Pradesh, Telangana and Yanam. It is listed as the 15th the largest language in the world and known as the third most widely spoken language after Hindi and Bengali in India. Despite having a substantial number of speakers worldwide, in Malaysia the Telugu community who speaks this language is a sub-minority group of Indians which comprises only about 2.4 % of the total Indian population. The purpose of this study is to find out if the Telugu community in Klang Valley is still maintaining or has shifted/is shifting away to another language. Thus, this study aims to answer 3 research questions, which are to find out the language choice of the Telugu community in Klang Valley in domains such as home, social, entertainment, official and religious. Besides, it aims to investigate if there are any differences in language choice between the younger and older generation and finally it examines the main reasons for language maintenance or shift in the community. This study uses both quantitative and qualitative approach. A quantitative approach is conducted on 100 Telugu participants who reside in Klang Valley to obtain statistical information. To further strengthen the findings, interviews were carried out with 10 participants. The interviews focus on the reasons behind language maintenance and shift among the Telugu community in Klang Valley. The findings show that the Telugu language is slowly shifting away mainly to English among the younger generation as English is viewed to be very important for educational, economical and career advancement. However, steps for language revival have been taken by Telugu Association of Malaysia (TAM) and it’s slowly being revived among the younger generation. As for the older generation, the language and the culture are still strongly embedded in their life. In general the majority of Telugus in Klang Valley still have a high regard towards their mother tongue and culture.